1993
DOI: 10.1016/s0006-3495(93)81255-4
|View full text |Cite
|
Sign up to set email alerts
|

An electron spin resonance study of interactions between gramicidin A' and phosphatidylcholine bilayers

Abstract: The model of microscopic order and macroscopic disorder was used to stimulate electron spin resonance spectra of spin-labeled lipids, 5-PC, 10-PC, and 16-PC in multilamellar vesicles of dipalmitoylphosphatidylcholine (DPPC) containing gramicidin A' (GA) at temperatures above the gel-to-liquid crystal transition of DPPC. The simulations show that at a lower concentration of GA (i.e., molar ratios of DPPC/GA greater than 3), GA has only a slight effect on the acyl chain dynamics. The rotational diffusion rate ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
74
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(82 citation statements)
references
References 38 publications
8
74
0
Order By: Relevance
“…We attribute the increase to an enlargement in the amplitude or rate of the random walk motion (particularly R ⊥ ) and a decrease in the overall alignment of the oriented bilayer discs caused by the increase in temperature. Previous solid-state NMR studies of lanthanide-doped bicelles indicate that phase instability can occur at temperatures greater than 50• C, which would lead to a decrease in bicelle alignment (36)(37)(38). This is also justified by the least-squares simulations shown in Fig.…”
mentioning
confidence: 52%
“…We attribute the increase to an enlargement in the amplitude or rate of the random walk motion (particularly R ⊥ ) and a decrease in the overall alignment of the oriented bilayer discs caused by the increase in temperature. Previous solid-state NMR studies of lanthanide-doped bicelles indicate that phase instability can occur at temperatures greater than 50• C, which would lead to a decrease in bicelle alignment (36)(37)(38). This is also justified by the least-squares simulations shown in Fig.…”
mentioning
confidence: 52%
“…The more motionally restricted component (b) is usually assigned to the boundary lipids contacting the GA aggregates [22][23][24][25], in analogy with similar studies on integral transmembrane proteins [26]. The weakly immobilized component (f) corresponds to the fluid (free) lipids, although the EPR spectra of the latter indicate considerably lower rotational mobility as compared with membranes of fluid lipids alone.…”
Section: Lipid-peptide Complexes: Interaction Of Gramicidin a With Dmmentioning
confidence: 79%
“…In previous studies [22][23][24][25], mostly on membranes with rather high gramicidin A contents (GA/lipid P 0.1 mol/mol), it was found that the conventional low-power EPR absorption spectra of phospholipids spin-labelled close to the terminal methyl group of the sn-2 chain contain two components. The more motionally restricted component (b) is usually assigned to the boundary lipids contacting the GA aggregates [22][23][24][25], in analogy with similar studies on integral transmembrane proteins [26].…”
Section: Lipid-peptide Complexes: Interaction Of Gramicidin a With Dmmentioning
confidence: 98%
“…Esser and Lanyi [65], investigating properties of the lipid phase in cell envelope vesicles from Halobacterium cutirubrum , were the first to note, that membrane integral proteins can decrease hydrophobicity of the membrane. Freed’s group showed that gramicidin A significantly decreased hydrophobicity of PL membranes [66, 67]. Based on these works Ge and Freed [67] suggested that it might be a general rule that integral membrane proteins and membrane soluble peptides decrease the hydrophobicity of membrane interior.…”
Section: Lens Fiber-cell Homeostasismentioning
confidence: 99%
“…Freed’s group showed that gramicidin A significantly decreased hydrophobicity of PL membranes [66, 67]. Based on these works Ge and Freed [67] suggested that it might be a general rule that integral membrane proteins and membrane soluble peptides decrease the hydrophobicity of membrane interior. Later works showed, however, that transmembrane peptides affect membrane hydrophobicity differently, depending on their structure and amino acid composition.…”
Section: Lens Fiber-cell Homeostasismentioning
confidence: 99%